A case study investigation into drama in education as an effective teaching methodology to support the goals of outcome based education - Elliott, Terri Anne (Rhodes University, Faculty of Humanities, Department of Drama, 2011)
The introduction of outcomes based education (OBE) in the form of Curriculum 2005 (C2005), the National Curriculum Statement (NCS) and the Revised National Curriculum Statement (RNCS) in post-apartheid South Africa resulted in a shift from a content-centred to a learner-centred view on education. This transition took place rapidly as the new government wanted to introduce a democratic education system after the divisive Bantu education system from Apartheid. However, after the changes were implemented, education in South Africa was theoretically outcomes based but practically many educators were still teaching in a content-centred manner. The research puts forward the proposal that drama-in-education (D-i-E) is a useful means by which to align the practical and theoretical goals of OBE within the context of South Africa's current RNCS. This hypothesis drives the main research question: "Can D-i-E be an effective teaching methodology to realise the goals of the RNCS and generate OBE learning environments in a South African high school?" D-i-E is a learner-centred teaching methodology and in practise it meets many of the goals and Critical Cross-Field Outcomes (CCFOs) of OBE. Some of these include the fact that learners can: "¢ Practice problem-solving skills; "¢ Engage with critical and creative thinking; "¢ Grow cultural and aesthetic sensitivity; "¢ Work effectively in groups; and ii. "¢ Learn in inclusive environments that cater for different learning styles and levels. The research examines the use of D-i-E as an outcomes based methodology by which the RNCS could be implemented in the classroom. This is explored through the use of qualitative research in the form of a case study investigation at a South African high school. The case study was conducted with Grade 11 and Grade 12 Dramatic Arts learners and involves an analysis of a D-i-E approach to learning. The conclusion that D-i-E is an effective outcomes based teaching methodology which could assist educators in realising the RNCS was largely reached through participant observation of D-i-E classes and by analysing the learners' journals in which they reflected on D-i-E experiences. The learners' feedback about the experience was generally positive and they reflected that they found D-i-E beneficial because of the fact that it engaged them experientially. They also reflected that D-i-E provided them with a more meaningful and exciting way of learning. These findings are however only generalisable to the type of context (Dramatic Arts learners from a well-resourced girls' high school) in which the research was conducted. The findings provide detailed insight into a specific case study and may be beneficial to educators in South Africa who aim to make use of the same or similar methodologies in their classroom practice. D-i-E also supports many of the underlying tenants of OBE such as learner-centredness, learner diversity and inclusive learning, and can effectively aid educators in implementing the RNCS in an outcomes based way.
Keywords: Drama in education -- South Africa; Competency based education -- South Africa; Curriculum planning -- South Africa; Student centered learning -- South Africa; Critical thinking -- Study and teaching -- South Africa